2018
DOI: 10.1146/annurev-anthro-102317-050322
|View full text |Cite
|
Sign up to set email alerts
|

Police and Policing

Abstract: The anthropology of policing draws from a range of intellectual traditions to generate new understandings of the police as an institution and policing as a social practice. This article reviews recent anthropological work on police, situating it in longer-term disciplinary concerns. I begin with the connection between policing and personhood, exploring how the subject–object dynamics of police domination are related to anthropological conceptions of kinship, law, and social control. I then turn to the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Neighborhoods with the norm (not) to cooperate: Evidence from ethnographic studies While studies have found significant variation across neighborhoods in willingness to cooperate with police, no quantitative study has addressed the possibility that some of this variation arises from placebased social norms. This is surprising, in part because ethnographic studies have shown considerable variability between communities in norms of cooperation with authorities (for a review, see Martin, 2018). For instance, Stoutland (2001) conducted in-depth interviews with community members in four high-violence neighborhoods in Boston, all of which had been affected by a rise in youth violence.…”
Section: Why Do People Cooperate With the Police?mentioning
confidence: 99%
“…Neighborhoods with the norm (not) to cooperate: Evidence from ethnographic studies While studies have found significant variation across neighborhoods in willingness to cooperate with police, no quantitative study has addressed the possibility that some of this variation arises from placebased social norms. This is surprising, in part because ethnographic studies have shown considerable variability between communities in norms of cooperation with authorities (for a review, see Martin, 2018). For instance, Stoutland (2001) conducted in-depth interviews with community members in four high-violence neighborhoods in Boston, all of which had been affected by a rise in youth violence.…”
Section: Why Do People Cooperate With the Police?mentioning
confidence: 99%
“…While studies have found significant variation across neighborhoods in willingness to cooperate with police, no quantitative study has addressed the possibility that some of this variation arises from place-based social norms. This is surprising, in part because ethnographic studies have shown considerable variability between communities in norms of cooperation with authorities (for a review, see Martin 2018). For instance, Stoutland (2001) conducted in-depth interviews with community members in four high-violence neighborhoods in Boston, all of which had been affected by a rise in youth violence.…”
Section: Neighborhoods With the Norm (Not) To Cooperate: Evidence Fromentioning
confidence: 99%
“…Expressions and repressions of violence do not stand alone but are shaped by social structures, ideologies and ideas (Ibid.). In that regard, the violence taking place between a policeman and a policed individual is situated within specific historical and cultural conditions of possibility (Martin, 2018). A police officer can be understood as a street-level bureaucrat, who is licenced to manage the state's legitimate monopoly on violence by using discretionary power to manage the problems in which he is implicated (Martin, 2018).…”
Section: Narratives Of Violencementioning
confidence: 99%